2019
DOI: 10.1016/j.jinf.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of invasive Haemophilus influenzae isolates in France and the emergence of resistance to third generation cephalosporins by alteration of ftsI gene

Abstract: High diversity of invasive Haemophilus influenzae isolates in France and the emergence of resistance to third generation cephalosporins by alteration of ftsI gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
5
43
0
Order By: Relevance
“…Isolates were cultured onto polyvitex chocolate agar plates and incubated at 37 C in 5% CO 2 for 18-24 h. DNA extraction for polymerase chain reaction (PCR) and next-generation sequencing were performed as previously described (Deghmane et al, 2019).…”
Section: Bacterial Growth Dna Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolates were cultured onto polyvitex chocolate agar plates and incubated at 37 C in 5% CO 2 for 18-24 h. DNA extraction for polymerase chain reaction (PCR) and next-generation sequencing were performed as previously described (Deghmane et al, 2019).…”
Section: Bacterial Growth Dna Preparationmentioning
confidence: 99%
“…Haemophilus species were initially identified by colony morphology, Gram stain and requirement for growth factors (V-, X-and XV-factors). PCR of the ompP2, bexA, fucK, iga, and hpd genes was applied as previously described (Deghmane et al, 2019). Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) Biotyper, version 3.0 (Bruker Daltonics, Champs sur Marne, France) was performed as previously described (Hong et al, 2019).…”
Section: Bacterial Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, public health authorities never reported suspicious clusters of NTHi cases during the observation time. A recent study revealed high diversity of NTHi in France [ 33 ]. Future analyses are needed to detect spatio-temporal clusters that include genomic typing of NTHi.…”
Section: Discussionmentioning
confidence: 99%